Mortalidad en exceso por hipertensión arterial y diabetes tipo 2 durante el periodo de pandemia por COVID-19 en el año 2020, en relación a los años 2015-2019, en Ecuador - Barrera Guarderas, Juan Francisco (2022)
Introduction: Diabetes Mellitus and Arterial Hypertension are chronic noncommunicable diseases that progress over the years, and are the most prevalent in mortality before and during the pandemic. Objective: The objective of this work is to determine the excess mortality from these causes during the year 2020 (with respect to mortality from these in the years 2015 - 2019) in Ecuador and its associated factors. Methods: The study was carried out with a time series design.